Analisis Sensoris dan Angka Lempeng Total (ALT) Kupang Krispi di UD. Bunda Foods - Fani Dukiandrian; Senja Ikerismawati (Jurnal Biosilampari : Jurnal Biologi, 2025)
Local seafood-based snacks have gained increasing popularity in Indonesia, yet their quality and safety assessments remain limited. Kupang krispi, a deep-fried mussel-based product produced by UD. Bunda Foods, represents a novel snack innovation that necessitates standardized evaluation. This study aimed to assess the sensory quality and microbiological safety of kupang krispi based on the Indonesian National Standard (SNI) 8272:2016. A descriptive quantitative approach was applied using two main analyses: sensory testing and total plate count (TPC). Sensory evaluation was conducted on two variants—Original and Spicy—covering attributes of color, aroma, texture, and taste using a 9-point hedonic scale by semi-trained panelists. Results indicated that both variants failed to meet the minimum sensory quality thresholds, with aroma receiving the lowest scores. The Spicy variant showed a marginally higher taste score (mean = 6.1) compared to Original (mean = 5.8), but both remained below the acceptable level of 7. Microbiological analysis showed TPC values ranging from 3.7×10³ to 4.5×10³ CFU/g, well below the maximum limit of 1×10⁵ CFU/g as set by the standard, indicating that the products are microbiologically safe for consumption. In conclusion, while the product is microbiologically compliant, sensory improvements are necessary through recipe reformulation and process enhancement.